Pengakuan Dan Pengukuran Pendapatan Berdasarkan Psak No 23 - Ella Zefriani Lisna; Liza Widya Hasyim (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2023)
Therefore, researchers are interested in conducting research that discusses "Accounting Treatment of Income in Travel Companies in Medan City Based on PSAK No. 23". This research was conducted with the aim of determining whether the method of recognition and measurement of income has been applied based on PSAK No. 23 by PT Sarena Wisata Tour & Travel Medan. To answer this question, this research is directed to research with a descriptive and comparative approach. Meanwhile, the data needed in this study is traced through primary data through interview techniques and secondary data that have been collected and processed by the company, for example income statements, official documents available at the company, related books and literature such as sales reports, and others. The results of the research that the author has obtained at PT Sarena Wisata Tour & Travel Medan, namely that basically its application has not been fully in accordance with generally accepted accounting standards.